Crystal structure of (E)-4-{2-[4-(allyloxy)phenyl]- diazenyl}benzoic acid - Rahman, Md. Lutfor; Mohd. Yusoff, Mashitah; Ismail, Jamil; Huey, Chong Kwong; Ching, Kheng Quah (International Union of Crystallography, 2014)
The title compound, C16H14N2O3, has an E conformation about the azobenzene [—N N– = 1.2481 (16) A ° ] linkage. The benzene rings are almost coplanar [dihedral angle = 1.36 (7)]. The O atoms of the carboxylic acid group are disordered over two sets of sites and were refined with an occupancy ratio of 0.5:0.5. The two disordered components of the carboxylic acid group make dihedral angles of 1.5 (14) and 3.8 (12) with the benzene ring to which they are attached. In the crystal, molecules are linked via pairs of O—H O hydrogen bonds, forming inversion dimers. The dimers are connected via C—H O hydrogen bonds, forming ribbons lying parallel to [120]. These ribbons are linked via C—H interactions, forming slabs parallel to (001).